ETIKA KEILMUAN DALAM PENELITIAN: MENJAGA INTEGRITAS AKADEMIK DI TENGAH GLOBALISASI DAN DIGITALISASI - Luthfiyah, Hullatul; Andayani, Nita Dwi; Fitriah, Ulfa Laelatul (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to analyze the application of scientific ethical principles in maintaining research integrity in the digital era. The method used is a literature review with a descriptive-analytical approach, collecting and analyzing 75 relevant articles (2020–2024) from scientific journals and academic publications. The findings highlight the importance of scientific ethics—honesty, transparency, and accountability—amid challenges such as plagiarism and data manipulation driven by digitalization. Higher education institutions play a crucial role in instilling ethical values, though implementation gaps remain. Technology offers solutions through anti-plagiarism software. In conclusion, scientific ethics enhance research credibility and institutional reputation. Recommendations include strengthening ethics training and utilizing technology to support research transparency.